2017
DOI: 10.1002/slct.201601732
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Titana‐ and Zirconadihydrofuran Metallacycles with Organoaluminium Compounds and Catalytic Activity of the Resulting Complexes in Polymerization of ϵ‐Caprolactone

Abstract: The interaction of the titanadihydrofuran metallacycles Cp2Ti[η2‐C(SiMe3)=C(Ph)‐C(Me)2O] (1) and Cp2Ti[η2‐C(SiMe3)= C(Ph)‐CH(Ph)O] (2) with iBu2AlH in n‐hexane at 20°C yields 1 : 1 complexes Cp2Ti[η2‐C(SiMe3)=C(Ph)‐C(Me)2O](iBu2AlH) (4) and Cp2Ti[η2‐C(SiMe3)=C(Ph)‐CH(Ph)O](iBu2AlH) (5) respectively. According to X‐ray diffraction data, the iBu2AlH molecule in 4 is coordinated by its aluminium centre with the oxygen atom whereas the hydride hydrogen atom of the iBu2AlH forms a bridge with the titanium. As a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Recently, we found that the reaction of a zirconadihydrofuran with HAl(i-Bu) 2 gave a 1:1 complex where, in addition to the coordination of the aluminium atom to the oxygen of the intact furan ring, a Zr-H-Al bridge was obtained. This compound also behaves as an active catalyst in the ROP of "-caprolactone (Burlakov et al, 2017). In addition, a zwitterionic hafnocene furanone-B(C 6 F 5 ) 3 adduct has been synthesized and structurally characterized (Beweries et al, 2009).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Recently, we found that the reaction of a zirconadihydrofuran with HAl(i-Bu) 2 gave a 1:1 complex where, in addition to the coordination of the aluminium atom to the oxygen of the intact furan ring, a Zr-H-Al bridge was obtained. This compound also behaves as an active catalyst in the ROP of "-caprolactone (Burlakov et al, 2017). In addition, a zwitterionic hafnocene furanone-B(C 6 F 5 ) 3 adduct has been synthesized and structurally characterized (Beweries et al, 2009).…”
Section: Chemical Contextmentioning
confidence: 99%